Cost benefit analysis of alternative testing and quarantine policies for travelers for infection control: A case study of Singapore during the COVID-19 pandemic - Lou, Jing; Lim, Nigel Wei-Han; Cai, Celestine Grace XueTing; Dickens, Borame Sue Lee; Huynh, Vinh Anh; Wee, Hwee-Lin (Frontiers in Public Health, 2023)
Background: Border control mitigates local infections but bears a heavy economic cost, especially for tourism-reliant countries. While studies have supported the efficacy of border control in suppressing cross-border transmission, the trade-off between costs from imported and secondary cases and from lost economic activities has not been studied. This case study of Singapore during the COVID-19 pandemic aims to understand the impacts of varying quarantine length and testing strategies on the economy and health system. Additionally, we explored the impact of permitting unvaccinated travellers to address emerging equity concerns. We assumed that community transmission is stable and vaccination rates are high enough that inbound travellers are not dissuaded from travelling. Methods: The number of travellers was predicted considering that longer quarantine reduces willingness to travel. A micro-simulation model predicted the number of COVID-19 cases among travellers, the resultant secondary cases, and the probability of being symptomatic in each group. The incremental net monetary benefit (INB) of Singapore was quantified under each border-opening policy compared to pre-opening status, based on tourism receipts, cost/profit from testing and quarantine, and cost and health loss due to COVID-19 cases. Results: Compared to polymerase chain reaction (PCR), rapid antigen test (ART) detects fewer imported cases but results in fewer secondary cases. Longer quarantine results in fewer cases but lower INB due to reduced tourism receipts. Assuming the proportion of unvaccinated travellers is small (8% locally and 24% globally), allowing unvaccinated travellers will accrue higher INB without exceeding the intensive care unit (ICU) capacity. The highest monthly INB from all travellers is 2236.24m, with 46.69 ICU cases per month, achieved with ARTs at pre-departure and on arrival without quarantine. The optimal policy in terms of highest INB is robust under changes to various model assumptions. Among all cost-benefit components, the top driver for INB is tourism receipts. Conclusions: With high vaccination rates locally and globally alongside stable community transmission, opening borders to travellers regardless of vaccination status will increase economic growth in the destination country. The caseloads remain manageable without exceeding ICU capacity, and costs of cases are offset by the economic value generated from travellers.